Pelatihan E-Marketing Berbasis Website dan Media Sosial bagi Mitra Usaha Madina Aneka Subur - Andi Ayu Nurnawati; Aksal Mursalat; Ifadhila Ifadhila (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the e-marketing capacity of Usaha Madina Aneka Subur by creating a website and social media accounts that can be used for digital marketing of Trichoderma organic fertilizer products. The method for implementing this service was training, which consisted of preparation, implementation, and evaluation stages. The evaluation instrument for this activity used a questionnaire distributed via Google Forms and was analyzed using descriptive analysis. The results of this service activity showed that the e-marketing capacity of Usaha Madina Aneka Subur increased with the realization of websites and social media accounts that can used for digital marketing of Trichoderma organic fertilizer products. Service partners were also very pleased with the training materials, website, and social media accounts for digital product marketing strategies.